1998
DOI: 10.1590/s1516-31801998000500005
|View full text |Cite
|
Sign up to set email alerts
|

End-to-side neurorrhaphy with and without perineurium

Abstract: Objective:We compared end-to-side neurorraphy with and without the perineural sheath. Method: Twenty rats were used. The peroneal nerve was sectioned and the distal end was sutured to the lateral face of the tibial nerve. We removed the perineural sheath only on the right side, but not on the left side. The proximal end of the peroneal nerve was curved back approximately at a 100° angle and implanted into the adductor muscle. Six months later, the 14 surviving animals were submitted to electrophysiological tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 3 publications
0
34
1
5
Order By: Relevance
“…Viterbo et al also compared in the same experimental model SE with and without epi-perineurium window. The results in reinnervation demonstrated no significant morphological or electrophysiological differences 5 . Ballance et al 6 proposed a similar end-to-side neurrorhaphy with the distal end of the facial nerve to the lateral side of the spinal accessory nerve, but the facial movements were simultaneous to the shoulder.…”
Section: Introductionmentioning
confidence: 83%
“…Viterbo et al also compared in the same experimental model SE with and without epi-perineurium window. The results in reinnervation demonstrated no significant morphological or electrophysiological differences 5 . Ballance et al 6 proposed a similar end-to-side neurrorhaphy with the distal end of the facial nerve to the lateral side of the spinal accessory nerve, but the facial movements were simultaneous to the shoulder.…”
Section: Introductionmentioning
confidence: 83%
“…Before performing terminolateral neurorrhaphy, whether or not open a window on the perineurium or epineurium of the donor nerve which is necessary, and has been extensively discussed in the previous literature [69,70]. In fact, when there is no injury to the donor nerve, nerve regeneration can occur following endto-side anastomosis, but several experimental studies have shown that when the donor nerve had a fenestration, the effect of nerve regeneration was better [71][72][73][74].…”
Section: Epineurium or Perineurium Windowmentioning
confidence: 99%
“…12,13,29,[48][49][50]54 but not later from 4 up to 8 months after surgery. 16,51,53,64 Interestingly, if epineurial or perineurial windows were enlarged from 1 to 4 or 5 mm, respectively, then, also, the magnitude of axonal ingrowth into the recipient nerve was increased. 65,66 Subepineurial focal degeneration and demyelination of the donor nerve distal to the site of coaptation in experimental groups Notably, bimodality coefficient > 0.555 indicates that a distribution is bimodal 56 (but see Jackson, P.R., Tucker, G.T., and Woods, H.F. (1989).…”
Section: Kovač Ič Et Almentioning
confidence: 99%
“…[1][2][3][4][5][6] Functional motor and sensory reinnervation of target tissue was observed after such nerve repair in experimental mammals. [7][8][9][10][11][12][13][14][15][16] Also, several clinical case series suggest that some patients with extensive nerve injuries in the upper extremity, facial palsy, or neurinoma could benefit by such a treatment, although the results are quite unpredictable. 2,[17][18][19][20][21][22][23][24][25][26][27][28] The basic idea of end-to-side nerve coaptation is to achieve reinnervation of a denervated tissue by the collateral sprouting of uninjured axons from the donor nerve through the distal stump of the injured recipient nerve without sacrificing the innervation of the original targets of the donor nerve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation